Characterization of Lignocellulosic Biomass Samples in Omu-Aran Metropolis, Kwara State, Nigeria, as Potential Fuel for Pyrolysis Yields - Anthony O Onokwai; Imhade P Okokpujie; Emmanuel S Ajisegiri; Makanjuola Oki; Adeyinka O Adeoyeb; Esther T Akinlabi (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
This study deals with a preliminary investigation of biomass samples' physicochemical, structural composition, and thermal properties to aid the appropriate selection of biomass utilized for pyrolysis operation. The proximate, ultimate, structural composition and thermal analyses were conducted using seven lignocellulose biomass samples obtained in Ajase market, Ajasse Ipo, Kwara State, Nigeria, and Omu-Aran, Kwara State, Nigeria. Results showed that the average moisture contents (MC) ranged from 0.12 to 0.44%, and volatile matter (VM) ranged from 73.70 to 83.82%. Fixed carbon (FC) varied from 12.79 to 22.80%, and Ash contents varied between 01.20 to 5.52%. Similarly, the average carbon contents ranged from 45.11 to 50.00%. Hydrogen contents ranged from 5.38 to 6.15%, nitrogen contents varied between 0.20 to 1.24%, and oxygen contents from 43.79 to 48.51%. Also, sulphur contents varied between 0.01 to 0.19%, while the biomass species' average cellulose, hemicellulose, and lignin contents ranged from 28.34 to 45.80%, 25.83 to 34.01%, and 21.96 to 49.63% respectively. The high percentage of VM, C, H, HHV, ignitability index, cellulose, and hemicellulose content recorded in the biomass samples would enhance devolatilization reactivity, ignitability, and burn gases in the reactor, as well as a good production of hydrocarbons content during the pyrolysis process. Also, the low ash content would prevent harmful chemical deposits in the reactor during the pyrolysis process. It can be deduced that shea butter wood was best suited for biofuel generation, closely followed by sugarcane bagasse and palm kernel shell. At the same time, corn cobs possessed the least properties for the pyrolysis process.